Implementation of the Health-Related Fitness Model - Sheila Dwi Loviani; Yudha M Saputra; Hamidie Ronald; Nurlan Kusmaedi (STKIP Muhammadiyah Kuningan, 2022)
This study aims to see the effect of providing a health-related fitness model on the physical improvement and physical activity of SMK students. The method used in this study was experimental with a randomized control group pretest-posttest design. The sample used a random cluster sampling technique by selecting the experimental group and the control group, consisting of 33 students aged 16-17 years. The instruments used in this study were physical fitness test instruments, namely the Indonesian Physical Fitness Test (TKJI) and the International Physical Activity Questionnaire (IPAQ). The results showed this study indicates a change in students' understanding of the HRF model before and after treatment; there is an effect of using the HRF model on physical fitness tests and active lifestyles. There is a significant relationship between understanding HRF, physical fitness, and an active lifestyle of 0.457, which is sufficient. There was an effect of Health-related fitness on physical fitness and students' busy lifestyles. A good Health Related Fitness can have a significant impact both on yourself and on fellow friends, relatives, family, and other general public.